2010
DOI: 10.1007/s00268-010-0637-7
|View full text |Cite
|
Sign up to set email alerts
|

Pelvic Exenteration for Advanced and Recurrent Malignancy

Abstract: Multivisceral pelvic surgery is possible with acceptable morbidity and QoL. Thorough patient selection and multimodal therapy are necessary to attain maximum benefit.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
54
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(66 citation statements)
references
References 47 publications
(57 reference statements)
10
54
2
Order By: Relevance
“…The patients whose margin was negative had longer survival than whose margin positive. Our finding correlated with the previous studies which found that surgical margin status was important risk factors to predict recurrence of the disease (Park et al, 2007;Zoucas et al, 2010). Park et al (2007) reviewed pelvic exenteration cases in an institute in Korea.…”
Section: Discussionsupporting
confidence: 90%
“…The patients whose margin was negative had longer survival than whose margin positive. Our finding correlated with the previous studies which found that surgical margin status was important risk factors to predict recurrence of the disease (Park et al, 2007;Zoucas et al, 2010). Park et al (2007) reviewed pelvic exenteration cases in an institute in Korea.…”
Section: Discussionsupporting
confidence: 90%
“…The perioperative mortality following TPE has decreased from as high as 20 % before 2000 [9,10] to less than 5 % in recently reported case series [7,11,12]. In the present series, one operative death was noted in the earlier period, but there Fig.…”
Section: Discussioncontrasting
confidence: 51%
“…Among the 13 cases whose diverting stomas were successfully taken down, the median Jeorge-Wexner incontinence score [5] at 1-year post operation was 8 [4][5][6][7][8][9][10][11][12][13][14], which was no worse than that of very low anterior resection. Among the 18 cases that underwent neobladder reconstruction, 15 cases voided urine spontaneously with a post-void volume less than 50 mL.…”
Section: Functional Outcomementioning
confidence: 99%
“…TPEs are associated with significant perioperative morbidity (38.4%-70%) and a reported mortality rate lower than 5% in recent publications [47,48,[93][94][95][96][97][98].…”
Section: Hemipelvectomy For Sarcomas or Metastaticmentioning
confidence: 99%